2019
DOI: 10.1038/s41419-019-1571-8
|View full text |Cite
|
Sign up to set email alerts
|

Neural stem cell-derived small extracellular vesicles attenuate apoptosis and neuroinflammation after traumatic spinal cord injury by activating autophagy

Abstract: Spinal cord injury (SCI) can cause severe irreversible motor dysfunction and even death. Neural stem cell (NSC) transplantation can promote functional recovery after acute SCI in experimental animals, but numerous issues, including low-transplanted cell survival rate, cell de-differentiation, and tumor formation need to be resolved before routine clinical application is feasible. Recent studies have shown that transplanted stem cells facilitate regeneration through release of paracrine factors. Small extracell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
199
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 248 publications
(213 citation statements)
references
References 70 publications
13
199
0
1
Order By: Relevance
“…Recent studies show that autophagy influences the recovery of motor function following SCI. 25,26 It is also involved in numerous neurodegenerative illnesses as well as in ischemic and traumatic brain damage. 27 Several studies show that autophagy is essential to the regulation of cell homeostasis as it acts as a quality control process for cellular biomolecules.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies show that autophagy influences the recovery of motor function following SCI. 25,26 It is also involved in numerous neurodegenerative illnesses as well as in ischemic and traumatic brain damage. 27 Several studies show that autophagy is essential to the regulation of cell homeostasis as it acts as a quality control process for cellular biomolecules.…”
Section: Discussionmentioning
confidence: 99%
“…Severe neuronal apoptosis is an outcome of stroke, especially in aged animals . Roles for NSC‐EVs on augmenting the ratio for neuronal survival/apoptosis is reported so far for Parkinson and spinal cord injury (SCI), and the results were promising. Combining with our findings, we could assert that NSC‐EVs‐based intervention is capable of protecting neurons threatened by brain ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…[35][36][37][38]. Our studies have shown that exosomes derived from MSCs could enhance functional recovery after SCI by inhibiting neuroinflammation and promoting axonal regeneration [39,40]. A clinical trial was developed to evaluate the effects of MSC-derived exosomes on the possible treatment of type I diabetes mellitus (Clini-calTrials.gov, NCT02138331) and the first patient has successfully been treated with MSC exosomes in graft versus host disease [41].…”
Section: Introductionmentioning
confidence: 99%